Physiotherapy management of Parkinson’s disease in a tertiary hospital in Nigeria: a case report - Moses Ayomide Olayemi; Rukayat Ajoke Bello; Olawale Isreal Oshomoji; John Oluwadunsin Adeolu (Bulletin of Faculty of Physical Therapy)
Abstract Parkinson’s disease (PD) is a progressive neurodegenerative disorder primarily characterized by the degeneration of dopaminergic neurons in the substantia nigra, leading to motor impairments such as tremors, bradykinesia, and postural instability. It also affects cognitive functions, contributing to difficulties in movement control and non-motor symptoms, including cognitive decline, sleep disturbances, and emotional dysregulation. Although pharmacological treatments provide symptomatic relief, there is limited evidence regarding the effectiveness of non-pharmacological interventions in improving both motor and cognitive outcomes. This case report details the physiotherapy management of a 72-year-old male patient with stage 3 PD, highlighting a structured 14-week physiotherapy program that targeted balance, coordination, and cognitive function. The intervention, which incorporated personalized exercises and cognitive training, resulted in significant improvements in tremor frequency, postural control, and cognitive function. Remarkably, the patient demonstrated a progression from Hoehn and Yahr stage 3 to stage 1, suggesting that intensive physiotherapy can have a profound impact on both motor control and overall quality of life (QOL). This case is notable for its novel approach in combining physical therapy with cognitive interventions in a PD patient, a strategy not widely reported in existing literature. Given the lack of curative treatments for PD, the findings underscore the critical role of non-pharmacological interventions, such as physiotherapy, in improving both motor and non-motor outcomes in PD patients. This report highlights the potential for intensive, individualized physiotherapy programs to promote neuroplasticity and significantly enhance patient outcomes, offering new insights into holistic PD management.